1994
DOI: 10.2105/ajph.84.3.388
|View full text |Cite
|
Sign up to set email alerts
|

Changes in HIV-related information sources, instruction, knowledge, and behaviors among US high school students, 1989 and 1990.

Abstract: OBJECTIVES. Few data have been available among adolescents to determine behavioral changes that may prevent human immunodeficiency virus (HIV) infection. This analysis examines changes in the prevalence of self-reported HIV-related information sources, instruction, knowledge, and behaviors among high school students in the United States. METHODS. Two independent, multistage national probability samples of students in grades 9 through 12 were surveyed in 1989 (n = 8098) and 1990 (n = 11,631) with self-administe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
1

Year Published

1996
1996
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 14 publications
0
12
1
Order By: Relevance
“…There should also be a big push to increase teaching efforts in schools. This type of information is also recommended in other studies [[23,26] and [27]]. There is considerable rationale to include HIV/AIDS education as an integral part of high school curriculum.…”
Section: Resultsmentioning
confidence: 92%
“…There should also be a big push to increase teaching efforts in schools. This type of information is also recommended in other studies [[23,26] and [27]]. There is considerable rationale to include HIV/AIDS education as an integral part of high school curriculum.…”
Section: Resultsmentioning
confidence: 92%
“…A study with students from a university in rural São Paulo revealed that 90% of young people said that transmission may occur through injectable drugs; 84% said through blood transfusion; 67%, said through sexual secretions; and 22% said through saliva 16 . However, literature shows that many young people still have doubts about vertical transmission and transmission through saliva and insect bites 16,17 . Although data collection instruments are different in the research on the subject, some of the questions about ways of transmission are seen in all of them 16,17 .…”
Section: Discussionmentioning
confidence: 99%
“…However, literature shows that many young people still have doubts about vertical transmission and transmission through saliva and insect bites 16,17 . Although data collection instruments are different in the research on the subject, some of the questions about ways of transmission are seen in all of them 16,17 .…”
Section: Discussionmentioning
confidence: 99%
“…Studies conducted since then have examined this topic among adolescents on several health issues including HIV-AIDS (Baird, 1993;Holtzman et al, 1994) and drug use (Mayton, Nagel, & Parker, 1990;Mirzaee, Kingery, Pruitt, Heuberger, & Hurley, 1991;and Lamarine, 1993). However, fewer studies have examined the sources of health information among adults on various health issues.…”
Section: Literature Summarymentioning
confidence: 99%